Association between adverse childhood experiences and adult diseases in older adults: a comparative cross-sectional study in Japan and Finland. Issue 8 (24th August 2019) - Amemiya, Airi; Fujiwara, Takeo; Shirai, Kokoro; Kondo, Katsunori; Oksanen, Tuula; Pentti, Jaana; Vahtera, Jussi
Abstract : Objective: We aimed to examine the association between adverse childhood experiences (ACEs) and diseases in older adults in Japan and Finland. Design: Cross-sectional comparative study. Setting: Data from a gerontological study in Japan and two public health studies in Finland were evaluated. Participants: A total of 13 123 adults (mean age, 69.5 years) from Japan and 10 353 adults (mean age, 64.4 years) from Finland were included in this study. Logistic regression was used to examine the association of each of, any of and the cumulative number of ACEs (parental divorce, fear of a family member and poverty in childhood; treated as ordered categorical variables) with poor self-rated health (SRH), cancer, heart disease or stroke, diabetes mellitus, smoking and body mass index. Models were adjusted for sex, age, education, marital status and working status. Results: Of the respondents, 50% of those in Japan and 37% of those in Finland reported having experienced at least one of the measured ACEs. Number of ACEs was associated with poor SRH in both countries, and the point estimates were similar (OR: 1.35, 95% CI: 1.25 to 1.46 in Japan; OR: 1.34, 95% CI: 1.27 to 1.41 in Finland). Number of ACEs was associated with the prevalence of cancer, heart disease or stroke, diabetes mellitus, current smoking and an increase in body mass index in both countries. Conclusions: The association between ACEs and poor SRH, adult diseases and health behaviours was similar among older adults in both Japan and Finland. This international comparative study suggests that the impact of ACEs on health is noteworthy and consistent across cultural and social environments.